Three-dimensional trunk adjustment based on surface markers in treating mild to moderate adolescent idiopathic scoliosis - Yao, Yanli; Han, Guangyan; Guo, Haibin; Ye, Chao; Wang, Xixi; Wang, Hui (Frontiers in Pediatrics, 2026)
Background Adolescent idiopathic scoliosis (AIS) has both physical and psychological impacts, requiring multidisciplinary non-surgical interventions. Incorporating three-dimensional (3D) adjustments may enhance the efficacy of traditional exercises. This study aimed to explore the clinical effect of integrating trunk 3D adjustments with conventional rehabilitation exercises in the treatment of children with mild to moderate AIS.MethodsThis study enrolled AIS patients treated at our hospital. Participants were assigned to either the combined therapy group, receiving trunk 3D adjustment and traditional rehabilitation, or the traditional therapy group, receiving traditional rehabilitation alone. The primary outcomes were the Cobb angle and angle of trunk rotation (ATR).ResultsA total of 46 children were included, 23 in each group, with median ages of 12 and 13 years for the traditional and combined therapy groups, respectively. Baseline characteristics showed no differences (all P > 0.05). After 6 months, the combined therapy group significantly improved in Cobb angle (7.00 vs. 10.00 degrees, P = 0.024) and ATR (3.26 ± 1.98 vs. 4.39 ± 1.78, P = 0.048), and showed better outcomes in forward head posture, shoulder asymmetry, and pelvic tilt (all P < 0.05).ConclusionThe integration of trunk 3D adjustment with conventional rehabilitation training effectively improves Cobb angle and ATR in mild to moderate AIS patients, highlighting the importance and potential of body alignment awareness for clinical treatment.